STORYTELLING IN TEACHING RUSSIAN AS A FOREIGN LANGUAGE: INTERPRETATION AND DEVELOPMENT OF BLAINE RAY’S METHOD - Kalbaev Amir Sapargaliy-uli (Western European Studies, 2025)
This article explores the implementation of storytelling techniques in teaching Russian as a foreign language, focusing on the interpretation and adaptation of Blaine Ray’s TPRS method. The study emphasizes the role of co-created narratives, comprehensible input, and digital storytelling in enhancing learner engagement, vocabulary retention, and intercultural competence. The paper also highlights the importance of grammar integration, the use of students’ native language, and emotional resonance in creating effective language learning environments. The findings support the inclusion of storytelling in RFL curricula at various educational levels.
Keywords: storytelling; Russian as a foreign language; TPRS